Sports: Social Inclusion or Racism and Xenophobia - Patsantaras, N; Kamberidou, I; Panagiotopoulos, P (Pandektis International Sports Law Review (IASL), 2008)
Violence and Racism in sport under the spotlight Sport federations, academics, politicians, and NGOs alike are sounding the alarm over the increase in violence and racism linked with sport events. In recent years we have seen many manifestations of racial intolerance and violence at football matches, converted into stages for regional and identity conflicts: (1) In Spain, racist right-wing supporters mocked and taunted black players. (2) In Greece, an Albanian fan was stabbed to death by a Greek at a qualifying match for the World Cup. (3) A referee was slashed by a missile at the Champions League match between Roma and Dynamo Kiev. (4) In the Netherlands, Dutch fans threw a smoke bomb into the Portuguese goal and firecrackers on to the pitch, hitting one of the players at the UEFA Cup match between Feyenoord of Rotterdam and Sporting Lisbon of Portugal. (5) German police used clubs and riot gas to arrest 46 fans after a minor regional league match between SSV Ulm of Germany and visiting FC Normannia Gmuend of Switzerland. (6) The violence in Milan, when two bitter rivals, Inter and AC, played in the quarter-finals for the Champions League, the top European club tournament, and (5) riots, such as those in the cities of Leipzig (Germany) and Catania (Italy), are the reason why the EU ministers responsible for sport are now closely studying the issue of sport and violence. Instead of focusing on enjoying sports, teaching youth pro-social attitudes and values through sports, or in reaping physical benefits, and instilling a lifelong involvement in athletics, we have been witnessing a notable increase of violent behaviour in stadiums, dehumanizing racist and xenophobic attitudes, hooliganism, doping, corruption, cheating, wheeling-and-dealing, political interference as well as the influence of big business, the media, sponsors, etc. Has sport lost its fun, and its positive social impact and values? Is it geared exclusively toward winning at all costs, and supporting obsessive competitiveness that leads to violence and racial conflicts?